Tinjauan Penggunaan Simbol dan Singkatan pada Rekam Medis Rawat Inap dalam Menunjang Akreditasi SNARS Edisi 1.1 di RSD Idaman Kota Banjarbaru - Nina Rahmadiliyani; Nor Chia (Jurnal Kesehatan Indonesia, 2020)
Symbols and abbreviations included to the standard of SNARS Edition 1.1 that found in hospital management standard groups that are Information Management and Medical Record (IMMR 12). The uniform use of diagnostic codes and procedures facilitates data collection and analysis in accordance with statutory regulations. The aim of this study is to consider the use of symbols and abbreviations in medical record of hospitalization to supporting the accreditation of SNARS Edition 1.1 at RSD Idaman Banjarbaru, Banjarbaru city. The method of this study is qualitative descriptive study. The instrument of this study uses interviews and observations guideline. The number of samples calculated using the Slovin formula was 332 medical records of inpatients that had symbols and abbreviations In this study using purposive sampling technique. The research subjects consisted of the main informant who was the head of the medical record installation while the triangulation informant was the officer for coding, indexing, and analysis. The results of this study showed that RSD Idaman Banjarbaru city already has their own regulations or rules about the use of symbols and abbreviations those are SOP and guide books of symbols and abbreviations. The regulation of symbols and abbreviations has been carried out in inpatient medical record, but in this implementation there are still uses of symbols and abbreviations that should not be used, and also those that are not in the guidelines.The evaluation of the use of the proper symbols is 70,8% and the improper symbols is 29,2%. The percentage of proper abbreviations for diagnotics and acts is 60,2% and the improper abbreviations is 39,8%. The percentage of proper abbreviations for prescription drugs is 76,3% and the improper abbreviations is 24,7%.